2006
DOI: 10.1093/geronb/61.2.p102
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function, Working Memory, and Medication Adherence Among Older Adults

Abstract: The purpose of this study was to investigate the association between cognitive processes and medication adherence among community-dwelling older adults. Ninety-five participants (M = 78 years) completed a battery of cognitive assessments including measures of executive function, working memory, cued recall, and recognition memory. Medication adherence was examined over 8 weeks for one prescribed medicine by use of an electronic medication-monitoring cap. In a simultaneous regression, the composite of executive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
256
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(281 citation statements)
references
References 35 publications
15
256
2
8
Order By: Relevance
“…However, other studies stated that older patients are at increased risk of non-adherence due to age related factors such as workingmemory loss and impaired executive performance, in addition to their administering multiple medications. [29,23] In the current study, there was a statistically significant association between the educational level and the medication non-adherence. Higher percentage (79.6%) of non-adherence patients had only primary and/or secondary education.…”
Section: Discussionsupporting
confidence: 44%
“…However, other studies stated that older patients are at increased risk of non-adherence due to age related factors such as workingmemory loss and impaired executive performance, in addition to their administering multiple medications. [29,23] In the current study, there was a statistically significant association between the educational level and the medication non-adherence. Higher percentage (79.6%) of non-adherence patients had only primary and/or secondary education.…”
Section: Discussionsupporting
confidence: 44%
“…Indeed, lower neurocognitive function has been associated with nearly four times greater risk of medication noncompliance in older adults (29). Our finding that executive functioning, as measured by Trail Making Test part B, worsened after transplant may have important implications for patient management because executive functioning is predictive of self-management and objectively measured adherence among older adults (34). Indeed, previous studies among primary care patients have demonstrated that better executive function is associated with more than a 3-fold greater likelihood of medication adherence after adjustment for background ORIGINAL RESEARCH characteristics (35), and we have previously shown that poorer executive functioning before lung transplantation is associated with greater mortality after transplant (21).…”
Section: Discussionmentioning
confidence: 85%
“…Once we controlled for baseline level of function (including executive function) as well as other variables including years of education, the difference in adherence between African-American and white subjects was no longer significant. Optimal adherence depends on patients taking the prescribed medication at the right time and in the correct manner [55]. Beyond working memory and encoding and storage of information, the organization and planning needed for medication adherence requires intact executive function.…”
Section: Discussionmentioning
confidence: 99%